A Study of Yeats’ Poetry: Exploring the shift from persona to poet in Yeats' and Eliot's poetry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As we move from Eliot's early to later poetry, we trace a change from the poetry of the persona to the poetry of the poet. From Ash-Wednesday onwards, the poet comes in his proporiapersona to state what he so far has said in the persons of others. Eliot has already in Traditionand the Individual Talent said, only those who have personality andemotions know what it means to want to escape from these things.1 To make personal emotions impersonal, one needs to have what we like but of what we ought to like, Eliot comes to posit in Religion and Literature. The two kinds of having is attained when we need to be acutely aware of what we like and what we ought to like at once,' they are not only different but also the same. The first means knowing what we really feel the second involves understanding our shortcomings. The two forms of self-consciousness, Eliot adds, knowing what we are and what we ought to be, must go together.